Phytochemicals and antioxidant activity of leaf extract and callus cultures of Cinnamomum camphora L - Sajal Rasool; Kainat Rasool; Sheza Ayaz Khilji; Zahoor Ahmad Sajid (PLoS ONE, 2025)
Cinnamomum camphora L. is highly significant landscape tree known for its medicinal values and presence of secondary metabolites that have antioxidant, antimicrobial, anticancer, anti-inflammatory effects and widely utilized in pharmaceutical and cosmetic industry. Callus cultures of C. camphora have better antioxidant activity than extracts of naturally grown tree leaves. While there is significant lack of research about the potential of its in vitro callus cultures as a controlled and sustainable biotechnological alternative for mass production of bioactive compounds. The present work was aimed at comparative analysis of phytochemicals (phenolic and flavonoid) and antioxidant activities of calli and leaf extract of field grown camphor plant. To get in vitro germplasm, callus formation and direct shoot initiation was carried out and it was observed that MS medium supplemented with 0.1 mg L -1 thidiazuron (TDZ) + 0.5 mg L -1 2, 4-dichlorophenoxyacetic acid (2, 4-D) proved best for shoot initiation from nodal explant. MS medium fortified with various plant growth regulators was used for callus formation and best callus induction response (100%) from nodal and leaf explants was observed on 0.5 mg L -1 2, 4-D) + 2.0 mg L -1 6-Benzylaminopurine (BAP). Callus was successfully sub-cultured and this in vitro proliferated calli and fresh leaf extract of field grown plant were used for comparative study of phytochemicals. Results revealed that callus culture exhibited highest antioxidant enzyme activities compared to leaf extract and hence there was statistically significant ( P ≤ 0.05 ) difference. Similarly, peroxidase (31.12 UmL -1 of enzyme), superoxide dismutase (35.24 Umg -1 of protein), and catalase (58.6 UmL -1 of enzyme) also showing highest vales. In contrast, glutathione peroxidase activity (0.552 Umg -1 ) was comparatively higher in leaf extract. Additionally, callus cultures accumulated higher phenolic contents (1.106 mg GAE g -1 of FW) while flavonoid contents (7.87 mg CatE g -1 of FW) were higher in leaf extract. This investigation showed that in vitro conditions and the use of plant growth regulators in various combinations might be work as elicitors to enhance the phytochemicals and antioxidant enzymes in callus culture as compared to the leaf extract.